Identification of Two Mannoproteins Released from Cell Walls of a Saccharomyces cerevisiae mnn1 mnn9 Double Mutant by Reducing Agents - Moukadiri, Ismaïl (American Society for Microbiology, 1999)
In this report, we present the identification of the main polypeptides that are extracted from purified cell walls of a Saccharomyces cerevisiae mnn1 mnn9 strain by reducing agents. Treatment of the purified cell walls of this strain with β-mercaptoethanol releases several mannoproteins, of which three, with apparent sizes of 120, 45, and 40 kDa, are the most abundant. Analysis of the amino-terminal sequences revealed that the 120-kDa mannoprotein is Bar1p, the protease involved in the so-called barrier activity in yeast cells, and that the 45- and 40-kDa mannoproteins are the Kex2-unprocessed and Kex2-processed forms of the gene product of open reading frame (ORF) YJL158c, an ORF that belongs to the PIR (protein with internal repeats) family of genes, composed thus far of PIR1, PIR2/HSP150, and PIR3. Accordingly we have named this gene PIR4, and Pir4 denotes the 40-kDa Kex2-processed form of the mannoprotein. We have characterized Pir4 and have shown the feasibility of using it as a fusion partner for the targeting of recombinant proteins to the cell wall.